41. RESULTS OF SINGLE-PORT VIDEO ASSISTED THORACOSOPIC LOBECTOMY IN THE TREATMENT OF EARLY STAGE NON-SMALL CELL LUNG CANCER AT NATIONAL LUNG HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: Lung cancer is the leading cause of cancer death in Vietnam. Total endoscopic lobectomy is indicated for the treatment of suitable stage non-small cell lung cancer. At National Lung Hospital Uniport VATS thoracoscopic lobectomy has been routinely perform to treat early stage non small cell lung cancer. We conducted a study on patients undergoing laparoscopic lobectomy at National Lung Hospital to evaluate the feasibility and safety of the surgery.Methods: We conducted a study from January 2022 to December 2022 on 84 patients undergoing endoscopic lobectomy for non-small cell lung cancer at the National Lung Hospital.Results: Most of the patients were in early stage, there were 8 patients with stage IIIA, the average operating time was 180 minutes, the average hospital stay was 8,8 days. There was 01 case of bleeding and 1 case of prolonged air leakage after surgery.Conclusion: Uniport VATS thoracoscopic lobectomy at National Lung Hospital hospital shows feasibility and safety although there are still many problems to improve to improve the quality of treatment.
Keywords: Lung cancer, uniport , VATS thoracoscopic surgery, lobectomy.